Three wall-associated kinases required for rice basal immunity form protein complexes in the plasma membrane. (2nd April 2016) - Cayrol, Bastien; Delteil, Amandine; Gobbato, Enrico; Kroj, Thomas; Morel, Jean-Benoit
ABSTRACT: Receptor-like kinases (RLKs) play key roles in disease resistance, in particular basal immunity. They recognize patterns produced by the pathogen invasion and often work as complexes in the plasma membrane. Among these RLKs, there is increasing evidence in several plant species of the key role of Wall-associated kinases (WAKs) in disease resistance. We recently showed using rice ( Oryza sativa ) loss-of-function mutants of three transcriptionaly co-regulated Os WAK genes that individual Os WAKs are positively required for quantitative resistance to the rice blast fungus, Magnaporthe oryzae . This finding was unexpected since WAK genes belong to large gene families where functional redundancy is expected. Here we provide evidence that this may be due to complex physical interaction between OsWAK proteins.